2002
DOI: 10.1086/339769
|View full text |Cite
|
Sign up to set email alerts
|

On the X-Ray Emission of the Low-Mass Galaxy Groups

Abstract: It is shown that the low-mass groups obey the L x ∼ σ 4 v law deduced for galaxy clusters. The impression of the more shallow slope of the L x − σ v correlation for groups is created not by enhanced X-ray emission, but by underestimation of the radial velocity dispersion of some groups.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Moreover, there is an increasing scatter to smaller systems, since there are only a few galaxy tracers with which to estimate the dispersion. This scatter could be larger still in observational studies because of projection effects (Tovmassian, Yam, & Tiersch 2002).…”
Section: Velocity-dispersion Biasmentioning
confidence: 97%
“…Moreover, there is an increasing scatter to smaller systems, since there are only a few galaxy tracers with which to estimate the dispersion. This scatter could be larger still in observational studies because of projection effects (Tovmassian, Yam, & Tiersch 2002).…”
Section: Velocity-dispersion Biasmentioning
confidence: 97%
“…The third possibility is that much of the orbital motion of the galaxy groups takes place in the plane of the sky and does not contribute to the line of sight velocity dispersion. Tovmassian et al (2002) showed that it is expected to find elongation and an anisotropic velocity dispersion tensor in many systems, since groups generally form within cosmic filaments.…”
Section: X-bootesmentioning
confidence: 99%
“…For galaxies, such an assumption is very unlikely to be accurate, even taking into account the fact that early-type galaxies will have potentials determined by the density of the Universe at the redshift of last major merger rather than that at which the majority of their stellar population formed. In order to calculate R 200 , we assume a mean redshift of formation for ellipticals of z form = 2 (Kauffmann, Charlot & White 1996;van Dokkum & Franx 2001). Using this value, we can calculate R 200 as described in Balogh, Babul & Patton (1999) and Babul et al (2002), taking variation of overdensity with redshift from Eke, Cole & Frenk (1996).…”
Section: β Fit and Entropymentioning
confidence: 99%